Impact of the Second Palestinian Legislative Elections on Palestinian Democratic Transformations - Khalil Mohamad Mahmood Abu Arab (My University, 2008)
This study examined the impact of the second Palestinian legislative elections on Palestinian democratic transformations within the Palestinian society in the wake of the Islamic Resistance Movement (Hamas)'s winning of these elections. To this end, the researcher raised questions pertinent to the impact of these elections on the future of the Palestinian political system. The researcher also studied the variables which have affected the political system from the ratification of Oslo Accords to the second parliamentary elections which effected important changes in the Palestinian democracy. To answer the questions of this study, the researcher began with a survey of Oslo Accords in terms of their nature and their effect on the Palestinian society. The researcher specifically investigated how the Palestinians got engaged in the political process and its impact on the Palestinian political system. As a matter of fact, their Palestinian Israeli agreements in Oslo had affected the Palestinian political system and created a state of division within the Palestinian society inside and in the Diaspora. Nevertheless, the agreement made it possible for the Palestinians to establish the first Palestinian authority in their land. However, this authority did not have full sovereignty. The researcher also explained that these agreements had written off the Palestinians' demand for the restoration of the 1948 lands after their acceptance and recognition of the UN resolutions 242 and 338. The researcher then moved to discuss the nature of the Palestinian political system and the impact of that on the democratic transformations in the Palestinian society. To this end, the researcher examined the influence of the second Palestinian legislative elections in the Palestinian factions and forces. These elections and their results were a very important turning point in the Palestinian society. All Palestinian national factions and forces, except Islamic Jihad, participated in these elections landslide. The victory of Hamas in these elections was a political upheaval in the political system from being a one- party political system to a system characterized by political pluralism. This victory by Hamas in these legislation elections surprised all including Hamas itself. That stunning victory came after the democratic process to proved that the Palestinian people's option was not necessarily supportive of the foreign and American position. Smoothness and quiet, which accompanied these elections, also astonished observers and the public. The Palestinians individuals and institutions, took upon themselves to make these elections a success. No violations were reported during the election process. This made international observers consider what had happened a big change in the democratic course of the Palestinian people. The researcher concluded that these elections have contributed to the reinforcement of the state of democracy in the Palestinian society and this in turn was reflected in the Palestinian political reality. However, the changes in the aftermath of these elections had had a great impact on the role played by the state's institutions in effecting this change particularly after Hamas moved from opposition and resistance to authority take over, and Fatah movement's change of position from authority to partial opposition. Fatah, after the elections, continued to control the institutions and presidency but lost its parliamentary strength. Moreover, the political developments, in the wake of these elections, showed that the world had an ''appointment'' with change in the structure of the Palestinian authority. This change was met with international rejection of the results of ballots after Hamas had achieved a big victory. This clearly showed that the world was waiting for a type of democracy that would suit it. However, the results ''blew'' against the world's wishes. In spite of this negative reaction of the international community, the elections turned things upside down. They produced a new Palestinian democratic path after the people participated strongly in these elections which in turn made them capable of effecting the required change. The democratic transformation and the results of the second Palestinian legislative elections were the basic pillar on which this was based. The hypothesis of this study was that the elections and their results had played an outstanding role in effecting Palestinian democracy. After testing this hypothesis, it was found that the elections and their results have created a new reality after the participation of several major factions and forces. They all competed over the legislative council seats, thus reflecting a big democratic change in the Palestinian political system. The results of these elections have put an end to the hegemony of one faction in the Palestinian arena. These also reinforced the state of partnership between the different factions and force. The elections, it should be maintained, were held on the principle of competition between the parties and forces to change the political reality. This study ended with investigation into the required role, expected from the political forces in Palestinian arena, to create an equation or strike a balance between the political desires of the parties and forces and the desires of individuals who expressed their commitment to the democratic option.

عمدت هذه الدراسة إلى مناقشة تأثير الانتخابات التشريعية الفلسطينية الثانية على التحولات الديمقراطية داخل النظام السياسي، بعد أن فازت حركة المقاومة الإسلامية حماس بهذه الانتخابات، حيث تم طرح أسئلة تتعلق بتأثير هذه الانتخابات على مستقبل النظام السياسي الفلسطيني، ودراسة المتغيرات التي أصابت النظام السياسي منذ إبرام الفلسطينيين اتفاقية أوسلو وصولا إلى الانتخابات الثانية، التي أحدثت تحولات هامة على الديمقراطية الفلسطينية. وفي الإجابة عن هذه الأسئلة تم استعراض اتفاقية أوسلو وماهية هذا الاتفاق وتأثير ذلك على المجتمع الفلسطيني، حيث تم بحث كيفية دخول الفلسطينيين هذه العملية وتأثير ذلك على النظام السياسي الفلسطيني، حيث اتضح أن هذا الاتفاق قد أثر على النظام السياسي وخلق حالة من الانقسام داخل المجتمع الفلسطيني، لكن الملاحظ أن هذا الاتفاق قد أوجد أول سلطة فلسطينية على الأرض لكنها سلطة ذات سيادة منقوصة، وبينت الدراسة أن هذا الاتفاق قد أسقط خيار المطالبة بأراضي عام 1948 بعد موافقة الفلسطينيين على قراري مجلي الأمن 242 و338. ناقشت الدراسة كذلك طبيعة النظام السياسي الفلسطيني وتأثير ذلك على التحولات الديمقراطية في المجتمع الفلسطيني، من خلال دراسة تأثير الانتخابات التشريعية الثانية على القوى والفصائل الفلسطينية، وأبرزت هذه الانتخابات تحولا هاما في المجتمع الفلسطيني والناجم عن مشاركة القوى والفصائل الوطنية في هذه الانتخابات وفوز حركة حماس بها، مما شكل انقلابا في النظام السياسي الذي خرج من إطار الحزب الواحد ليتحول إلى نظام تبرز فيه التعددية السياسية. أصاب فوز حماس ب الانتخابات التشريعية الكثيرين بالدهشة والاستغراب، الدهشة لهذا الفوز الكبير جاء بعد أن استطاعت العملية الديمقراطية أن تثبت أن خيار الشعب الفلسطيني ليس بالضرورة أن يكون مساندا للموقف الأجنبي والأمريكي، والاستغراب من السلاسة والهدوء التي مرت بها هذه الانتخابات،حيث تحمل الفلسطينيون أفرادا ومؤسسات المسؤولية على عاتقهم لإنجاح هذه الانتخابات بهذه الصورة، حيث لم تسجل أية خروقات للعملية الانتخابية الأمر الذي اعتبره المراقبون الدوليون بأن ما جرى تحولا كبيرا في المسار الديمقراطي الذي سطره الفلسطينيون بصورة مشرفة. وخلصت الدراسة إلى أن الانتخابات ساهمت في تعزيز الحالة الديمقراطية داخل المجتمع الفلسطيني، الذي انعكس بدوره على الواقع السياسي الفلسطيني، ولعل المتغيرات التي أعقبت الانتخابات التشريعية الفلسطينية كان لها أكبر الأثر على الدور الذي لعبته مؤسسات الدولة في إحداث التغيير، خاصة بعد أن انتقلت حركة حماس من المعارضة والمقاومة إلى السلطة وكذلك حركة فتح التي انتقلت من السلطة إلى المعارضة الجزئية، ففتح تسيطر على المؤسسات وكذلك على الرئاسة إلا أنها فقدت ب الانتخابات القوة التشريعية. وأظهرت التطورات السياسية التي أعقبت الانتخابات التشريعية الفلسطينية أن العالم كان على موعد مع التغيير الذي حصل في تركيبة السلطة الفلسطينية، هذا التغير رافقه رفض دولي لما ألت إليه نتائج صناديق الاقتراع، خاصة بعد أن حققت حماس هذا الفوز الكبير، ولعل ذلك يشير إلى أن العالم كان ينتظر تحقيق ديمقراطية تناسبه وإذا ظهر عكس ذلك فإن المقياس يختلف. لكن هذه الانتخابات أدت إلى قلب الموازين وأفرزت نهجا ديمقراطيا فلسطينيا جديدا، بعد أن شارك الفلسطينيون بقوة بهذه الانتخابات، التي جعلت منهم قادرين على إحداث التغير المطلوب، فعملية التحول الديمقراطي وما آلت إليه نتائج الانتخابات التشريعية الثانية كانت الركيزة الأساسية التي انطلقت منها هذه الأطروحة، لاسيما وأن فرضية هذه الدراسة قد أشارت إلى أن الانتخابات ونتائجها قد لعبت دورا بارزا في إحداث الديمقراطية الفلسطينية، وقد اتضح من خلال هذه الفرضية أن الانتخابات خلقت واقعا جديدا،بعد مشاركة العديد من القوى والفصائل في هذه الانتخابات، والتي تنافست على مقاعد المجلس التشريعي حيث عكس ذلك تحولا ديمقراطيا كبيرا في النظام السياسي الفلسطيني، لأنها أنهت هيمنة الفصيل الواحد على الساحة الفلسطينية، وعززت حالة من الشراكة بين القوى والفصائل والتي قامت على مبدأ التنافس بين القوى والأحزاب لتغيير الواقع السياسي، من أجل البحث في الدور المطلوب من القوى السياسية على الساحة الفلسطينية في إيجاد معادلة مابين الرغبات السياسية للقوى والأحزاب ورغبة الإفراد الذين عبروا عن تمسكهم بالخيار الديمقراطي.
أثر الإنتخابات التشريعية الفلسطينية الثانية على التحول الديمقراطي الفلسطيني